2010
DOI: 10.1007/s11431-010-4110-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polystyrene spheres in different particle sizes and assembly of the PS colloidal crystals

Abstract: Monodisperse polystyrene (PS) colloidal spheres were successfully prepared through emulsifier-free emulsion polymerization by controlling the polymerization reaction time, ionic strength of the system, concentration of the ionic copolymer (sodium p-styrenesulfonate) and other factors. The PS colloidal spheres were assembled into colloidal crystals whose structures were mainly face-centered cubic (fcc) close-packed. Then FDTD method was used to calculate the color-rendering characteristics of the colloidal crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(88 citation statements)
references
References 11 publications
5
82
0
1
Order By: Relevance
“…Polystyrene colloidal spheres with an average size of 290 ± 30 nm were prepared using emulsifier-free emulsion polymerization (Supporting Information). 12 From these nanospheres the template was self- assembled by evaporation ( Figure S2). 13 The sol−gel precursor mixture was aspirated into the nanosphere template and the sol−gel reaction was allowed to proceed, resulting in the formation of a silica matrix.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Polystyrene colloidal spheres with an average size of 290 ± 30 nm were prepared using emulsifier-free emulsion polymerization (Supporting Information). 12 From these nanospheres the template was self- assembled by evaporation ( Figure S2). 13 The sol−gel precursor mixture was aspirated into the nanosphere template and the sol−gel reaction was allowed to proceed, resulting in the formation of a silica matrix.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…35 %) was observed from g‐C 3 N 4 @PC‐FTO with respect to g‐C 3 N 4 @p‐FTO when the photoanode was rotated from 90° to 15° (Figure c), and enhanced current density per sun was obtained at 30° and 15° corresponding to a PSB blue edge (30°) and a PSB (15°) overlapped with g‐C 3 N 4 absorption region (Figure b), respectively. In a previous study, it was found that when the emission frequency of Tb 3+ ions is close to the PSB of silica photonic crystal, 40 % larger lifetime of PL decay was observed, this was concluded as the suppression of recombination. The difference in our PL decay curves of the g‐C 3 N 4 @PC‐FTO when the PL frequency of g‐C 3 N 4 overlapped or not overlapped with the PSB of PC‐FTO is obviously little (Figure d).…”
Section: Resultsmentioning
confidence: 94%
“…Under certain incident light angles, extra contributions arise from the random orientation of photonic crystal planes may lead to multiple PSB in the visible region. For instance, the ratio of the wavelength position of PSB from (200) plane is 0.866 in relative to that from (111) plane . Thus, the shoulder of PC‐FTO under 75° illumination (at 405 nm) in the DRUVS (Figure b) can be assigned to a PSB from (200) Bragg reflections.…”
Section: Resultsmentioning
confidence: 95%
“…The interfacial tensions between two polymeric components and water are negligible because of using surfactant41 ; so, the interfacial tension between PS seed particles and PPy oligomers would be most decisive parameter and in order to minimize the total interfacial free-energy it is necessary to form the least interfacial area between two polymeric components which results in the phase separation of PPy from PS particles and the formation of patchy and snowman-like Janus particles.Besides, FT-IR spectroscopy was utilized to conform the accuracy of polymerization in both stages.Figure 6presents FT-IR spectra of PS seed particles prepared with various surfactants and relating composite particles with the pyrrole/seed weight ratio of 1:6. The absorption bands at the wave numbers of 3066 and 3026 cm −1 correspond to stretching vibrations of aromatic C─H and the peaks of 1603, 1493, and 1450 cm −1 is attributed to the stretching vibrations of aromatic C C42,43 which is a strong evidence of the existence of benzene rings in the PS chains. The absorption bands at the wave numbers of 756 and 698 cm −1 are due to C─H out-of-plane bending vibration 44.…”
mentioning
confidence: 96%